(3TQM cTa GdCSQGQs - (3fLe GdOjf YeQ Hf Ydj GdbRhjfis; (3GaVd GdOjf eMeO Hf fGeGhQ Hf YHO Gdedc GdNhfLj,J (B649 (3g` s ((3eYJhb Hf eSYhO GdSejGWi s)
(3ChdgG (B:s
(3jHOC HGdaUd GdSGHY ai GdbVGjG GdTQWjI s
(3BNQgG (B:s
(3jfJgi HGdHMK GdKGfi ai JQcjH fcJ eZGdWI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs